Seguimiento de los egresados de la facultad de odontología de la universidad de Antioquia desde 1941 hasta el 2011. Parte II: caracterización laboral (2014)
ABSTRACT: The graduate follow-up should be part of any institutional mission; it is the duty of the university to observe the work performance of its graduates. The purpose of this second part of the research was to determine labor characterization, performing disciplinary areas, time spent, income, work contracts, type of contracts and social security. Methods: a descriptive, retrospective, cross-sectional study, with a structured survey, triangulated, validated and pilot. Ethical principles were respected and guaranteed the confidentiality of information. Results: most graduates who engage in the practice of dentistry perform clinical activities, together with other activities such as administration, teaching and research. Most clinical dentists work in clinics owned or leased, 35.9% spend more than 40 hours per week at work, the average salary is between $ 1.500.000-2.999.999 (43.1%), work independently, followed by associated or percentage earnings, the associated and independent dentists feel more satisfied. The 79.7% are listed for the Social Security System in Health, more than 50% have pension scheme, and few have severance fund, prepaid or occupational hazards health insurance. 9.4% are retired. Conclusions: the graduates are engaged in the practice of clinical dentistry and most of them are in the Social Security System, but few have occupational hazards insurance. They have different ways of contracting and labor contract. The salary depends on the their level of education, the time devoted and years since graduation. Regardless of salary, most are satisfied and do their work with pleasure.